Composite resins: a literature review (Research, Society and Development, 2022)
Composite resins have been present in dentistry for more than 50 years and are frequently improved due to their wide demand and clinical versatility. Its main use consists of direct restorations, mainly due to the current high aesthetic demand making it a material of first choice. However, the wide variety of resins and their differences in the properties of each product available on the market can make it difficult to decide which composite to use during clinical practice. The macro particulate resins had good mechanical capacity, however, low surface smoothness making polishing difficult, being more susceptible to pigmentation. Microfill composites show excellent aesthetic properties and surface smoothness, polishing and gloss, however, less mechanical properties. Hybrid and micro-hybrid resins combine mechanical and aesthetic properties satisfactorily, which leads some authors to mention them as universal restorative materials. Nanoparticulates or nanohybrids were introduced with the objective of further improving the properties of hybrid resins, also presenting excellent aesthetic and mechanical characteristics. Recently, bulk-fill resins appear with the premise of clinical practicality combined with properties similar to traditional resins. The objective of this work is to inform about composite resins, according to their charge particles, advantages, disadvantages and indications.